An assessment of the local sociocultural concept of climate change and its perceived effect on forestbased livelihoods : case study of rural communities of Vhembe District South Africa - Chirwa, Paxie W. (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.